The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2010
DOI: 10.1111/j.1439-0264.2009.00966.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistolocalization and Gene Expression of the Carbonic Anhydrase Isoenzymes (CA‐II and CA‐VI) in Glands Associated with the Canine Lacrimal Apparatus

Abstract: Summary Cytosolic and secretory carbonic anhydrase isoenzymes (CA‐II and CA‐VI, respectively) were detected by immunohistolocalization using specific canine CA‐II and CA‐VI antisera. CA‐II and CA‐VI were identified in glands associated with the canine lacrimal apparatus, such as lacrimal gland, superficial gland of the third eyelid (third eyelid gland) and tarsal gland. CA‐II and CA‐VI mRNA signals were also detected by reverse‐transcriptase polymerase chain reaction in the same tissues. Some serous acinar cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…In addition, clusters of acinar cells containing lipid granules are present in the periphery of the third eyelid gland, but not in the lacrimal gland. 30,45 The present study showed that both secretory cell types, classified as type T cells and type A cells, had different morphological and morphometrical features of the secretory granules. Furthermore, the secretory granules of the A cell type had a higher concentration of glycocojugates than those of the T cell type, as shown by the staining ability of the PA-TCH-SP-PD procedure.…”
Section: Discussionmentioning
confidence: 60%
“…In addition, clusters of acinar cells containing lipid granules are present in the periphery of the third eyelid gland, but not in the lacrimal gland. 30,45 The present study showed that both secretory cell types, classified as type T cells and type A cells, had different morphological and morphometrical features of the secretory granules. Furthermore, the secretory granules of the A cell type had a higher concentration of glycocojugates than those of the T cell type, as shown by the staining ability of the PA-TCH-SP-PD procedure.…”
Section: Discussionmentioning
confidence: 60%
“…No annotation data were generated for cluster 8 (no data). Veterinary Medicine International tarsal gland of dogs [22], but not in TF.…”
Section: Discussionmentioning
confidence: 89%
“…Of the 16 proteins identified, the authors confirmed in cats what has been already found in other studies who described the presence of lactotransferrin [41], serum albumin [11,23,43,44], two allergenic lipocalins [45,46], neutrophil gelatinase-associated lipocalin (NGAL) [47], and keratin [41] in other TF studies. ree proteins (carbonic anhydrase II [22], polymeric immunoglobulin receptor [48,49], and phosphoglycerate kinase [50]) have already been described in other structures of the lacrimal system. In addition, seven proteins (C1q/TNF-related secretory protein, three protein kinase family members, apelin receptor, α-1,4 glucan phosphorylase, and WD repeat domain 1) to our knowledge have never been observed in any lacrimal system structure, so they are described here for the first time.…”
Section: Discussionmentioning
confidence: 97%
“…Cytosolic CA6 is responsible for electrolyte and water secretion by the acinar cells in both salivary and lacrimal glands. CA6 in the secretory granules, on the other hand, is discharged into the acinar lumen to maintain bicarbonate levels to regulate pH in tear fluid and protect the corneal and conjunctival epithelial cells against injuries [25]. The significant association that we found between anti-CA6 and severe ocular surface staining can be explained either by reduced secretion or by changes in pH of the tear film which make epithelial cells vulnerable.…”
Section: Discussionmentioning
confidence: 95%
“…Carbonic anhydrases are responsible for regulation of acid-base balance in both physiological and pathological states [23]. CA6 is the only secretory isoenzyme of the carbonic anhydrase enzyme family expressed by parotid and submandibular glands as well as lacrimal glands [2325]. Cytosolic CA6 is responsible for electrolyte and water secretion by the acinar cells in both salivary and lacrimal glands.…”
Section: Discussionmentioning
confidence: 99%